Masalah-Masalah Moral Masyarakat di Surat Kabar: Studi Kasus terhadap Halaman â€œKasusâ€ di Surat Kabar Harian Kedaulatan Rakyat - Y. Agus Tridiatno (Jurnal ILMU KOMUNIKASI, 2006)
Abstract: Information delivered by the media makes the people to communicate each other focus on that information. In the long run, communication about the same object between the people will construct a certain community characterized by the ideology of the media. In this sense, communication media plays its role constructing a community. Besides, communication media can also present the social reality only. It does not build a community, but just portraits it. Newspaper can build a certain community with information published in it. But it can just portrait the social reality of its readers. Kedaulatan Rakyat, the oldest newspaper in Indonesia, of course plays the functions above. It builds a community of the readers or just portraits the social reality of society. This paper describes moral problems of the people portrayed byÂ Kedaulatan Rakyat especially its â€œKasusâ€ page. Economic moral cases stays in the first rank among others. The age of 26 up to 45 yearsâ€™ invidious is critical ages for doing immoral acts.